Penerapan Terapi Bermain Mewarnai Pada Anak Prasekolah (3-6 Tahun) Terhadap Kecemasan Akibat Hospitalisasi Di RSUD Dr Moewardi Surakarta - Ellenfika Lorenza; Maryatun Maryatun; Suciana Ratrinaningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
Background : Feelings of anxiety are the impact of hospitalization experienced by preschool children. This impact has the risk of disrupting the child's growth and development and the child's healing process. To reduce anxiety, children can be given play therapy. Hospitalization anxiety in children can make children difficult to eat, restless, afraid, restless, anxious, unwilling to cooperate in treatment, thus disrupting the child's healing process, the hospitalization period in preschool children can also cause post-traumatic stress disorder (PSTD) which makes children became traumatized while being treated in hospital. Purpose : To find out the results of anxiety values when applying coloring play therapy in Flamboyan Room 9, Dr. RSUD. Moewardi. Methods : The application was carried out using a descriptive case study method for 2 respondents and was carried twice every 3 day for 30 minutes. Result : Respondent 1, before being given coloring play therapy, obtained an anxiety score of 4 (moderately anxious) and after being given coloring play therapy it became 1 (very not anxious). Meanwhile, for Respondent 2, before being given coloring play therapy, the anxiety score was 5 (Severely Anxious) and after being given coloring play therapy it was 2 (Not anxious). Based on the results of the implementation that has been carried out, there is a reduction in anxiety due to hospitalization. Conclusion : Coloring play therapy can be used as a technique to reduce anxiety in preschool children due to hospitalization.